Biohydrogen Production from Crude Glycerol Using Anaerobic Mixed Cultures: Media Compositions Optimization - Sureewan Sittijunda (Science Faculty of Chiang Mai University, 2019)
The medium compositions for hydrogen production from glycerol derived from biodiesel production process were optimized using response surface methodology (RSM). The crude glycerol concentration, urea concentration, and Na2HPO4 concentration were found to have significant effects on hydrogen production by Plackett-Burman design. The path of steepest ascent method was employed to access the optimal region of the significant variable factors, followed by an application of RSM with Box-Behnken design. According to the RSM analysis, the optimum medium compositions were crude glycerol, urea, and Na2HPO4 in the concentrations of 4.04 g/L, 0.21 g/L, and 585.41 mg/L, respectively. Using this media, a maximum hydrogen production of 40.79 mmol H2/L was obtained. Microbial community analysis by polymerase chain reaction-denaturing gradient gel electrophoresis revealed that the predominant hydrogen producer in the fermentation broth was Megaspheara sp. The energy conversion efficiency from crude glycerol to hydrogen was 19.24%.